Nuclear-analytical and mineralogical principles and techniques for prediction and investigation of the native-pure rare isotope occurrence - Valter, A.A.; Storizhko, V.E.; Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Berlizov, A.N. (Вопросы атомной науки и техники, 2005)
Combining nuclear microanalytical, mineralogical, crystallochemical and geochemical approaches, the authors analyze a possibility of natural occurrence of enriched or even pure and superpure rare isotopes that can be extracted from ores. Methods of and results from the investigations of these isotope anomalies are presented.